A directional continuous wavelet transform of mode shape for line-type damage detection in plate-type structures. (15th March 2022) - Shi, Binkai; Cao, Maosen; Wang, Zijian; Ostachowicz, Wieslaw
Highlights: A analytical free vibration of long narrow notched plate model is proposed. A directional continuous wavelet transform of displacement mode shape for line-type damage detection is investigated. The optimal mother wavelet selection is proposed fully investigated. The experimental modal test is adopted using non-contact testing. Abstract: Line-type damage is abundant in engineering structures that have been in service for a long time. Vibration-based nondestructive testing as a global method has been extensively used in structural damage identification. In this study, a two-dimensional directional continuous wavelet transform (2D-DCWT)-based damage identification algorithm using "Morlet2d" wavelet for line-type damage detection in plate structures is presented. An analytical long narrow notch-type damage model of simply-supported plates is proposed to evaluate line-type damage effect on plate vibration performance. Based on the proposed model, the biggest challenge in parameter selection of wavelet analysis is solved. The fundamental aspects of 2D-DCWT algorithm in term of notch location and orientation are assessed. A multi-mode shape fusion approach is presented to make the 2D-DCWT algorithm apply to the high-order mode shapes. A comparative study with isotropic "Mexcan-hat2d" wavelet-based damage identification is performed, and it demonstrates that the proposed 2D-DCWT algorithm is superior in noise immunity. The efficiency and practicability of the 2D-DCWT algorithm are certified by an experimental modal test on damage detection of an artificially-induced notched aluminum alloy clamped plate using excitation-response system of the Piezoelectric Leadzirconate-Titanate (PZT) and Scanning laser Doppler Vibrometers (SLDV). As demonstrated in both the analytical and experimental investigation, the suggested approach may successfully identify line-type damage in plate-type structures.